A study on cardiac troponin t in early diagnosis of myocardial injury due to perinatal asphyxia and its comparison with other modalities - Tamilarasu, N.; Kumaravel, K. S. (International Journal of Contemporary Pediatrics, 2017)
Background: Perinatal Asphyxia is a multi-system disorder and its effects are not limited to central Nervous System. MODS determine the early outcome of asphyxiated neonate. Cardiac impairment occurs in about 25% of neonates with asphyxia. Often cardiac impairment is overlooked due to the lack of sensitive diagnostic test. Methods: A hospital based prospective analytical study performed over 50 Asphyxiated neonates admitted in our NICU from September 2016 to January 2017 myocardial dysfunction was evaluated using clinical, electrocardiography, echocardiography and cardiac troponin-T card test. Results: In the present study, among the 50 neonates 32 had clinical evidence of myocardial injury. Troponin T card test has the highest sensitivity of about 84.37%, positive predictive value of 93.1% and negative predictive value of 76% in diagnosing myocardial injury in contrast to ECG and ECHO. In terms of Specificity ECHO has the highest specificity of about 94.4% when compared to ECG and Trop T. Among all the diagnostic modalities used in this study, Troponin T best predicts the severity and outcome of Perinatal asphyxia. Conclusions: Troponin T card test is a valuable tool for early detection of myocardial injury due to perinatal asphyxia. In resource limited setting where the accessibility to 12 lead ECG, ECHO, and aid of cardiologist are not available, Trop T card test will serve as an effective handy screening tool in diagnosing myocardial injury